(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Generally, the financial sector divided in 2 parts, Money market as well as capital market. Securities market place is a crucial, structured capital industry where transaction of capital is facilitated using immediate funding with securities as an investment. Securities market can be split into a main market as well as secondary market.